Distorsi Visual: Membaca Ekspresionisme Affandi dalam Lukisan Potret Diri Menghisap Pipa (1977) - Achmad Maulana Yusuf; Muhammad Ilham Barik (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2026)
This study examines visual distortion, the use of emotional color, and expressive composition in Affandi's painting Self-Portrait Smoking a Pipe (1977), focusing on a systematic and contextual visual hermeneutic reading. The research background stems from the need to update the study of Indonesian expressionism through the integration of contemporary theories on visual perception, color psychology, and gestural analysis. This study aims to reveal how anatomical distortion, color dynamics, and non-linear compositional structures function as expressive strategies that reflect the artist's psychological condition and existential reflections in the final period of his life. The research method uses a descriptive qualitative approach and visual hermeneutic analysis through observation of digital documentation and a review of recent literature (2020–2025). The findings indicate that the distortion of shapes in the facial area and the finger-swiping gesture represent emotional tension, while the dominance of red, yellow, and green colors forms an affective spectrum that strengthens the psychological atmosphere in the work. The asymmetrical composition with diagonal lines creates a dynamic visual rhythm and directs the viewer's focus to the center of expression. The implications of the research emphasize that Affandi's works need to be read through a multidimensional approach that combines psychological, aesthetic, and hermeneutic aspects in order to obtain a more comprehensive understanding of his expressionist character.